The Effect of Audit Quality, Auditor Independence, and Financial Reporting Transparency on Internal Control Effectiveness: A Case Study of a Public Company in Indonesia - Trinandari Prasetyo Nugrahanti; Eko Sudarmanto; Mega Andani; Loso Judijanto (West Science Accounting and Finance, 2023)
This study investigates the intricate dynamics of corporate governance in publicly traded companies in Indonesia, focusing particularly on the interaction of Audit Quality, Auditor Independence, Financial Reporting Transparency, and Internal Control Effectiveness. The present study showcases the development of a comprehensive measurement model, hence offering empirical support for the reliability and validity of the chosen constructs. The utilization of structural equation modeling reveals statistically significant positive correlations, indicating that heightened levels of Audit Quality, Auditor Independence, and Financial Reporting Transparency are associated with enhanced Internal Control Effectiveness. The model fit assessment confirms the adequacy of the proposed structural equation model in capturing the observed covariance structure. The explained variance in Internal Control Effectiveness highlights the substantial impact of these governance elements. These findings offer valuable insights for stakeholders and policymakers seeking to fortify corporate governance practices in the Indonesian business landscape.